A comparison of two-coloured filter systems for treating visual reading difficulties. - Hall, R; Ray, N; Harries, P; Stein, J (2013)
PURPOSE: Visual disturbances that make it difficult to read text are often termed "visual stress". Coloured filters in spectacles may help some children overcome reading problems that are often caused by visual stress. It has been suggested that for optimal effect each child requires an individually prescribed colour for each eye, as determined in systems such as the "Harris Foundation" coloured filters. Alternatively, it has been argued that only blue or yellow filters, as used in the "Dyslexia Research Trust" (DRT) filter system, are necessary to affect the underlying physiology. METHOD: A randomised, double blind trial with 73 delayed readers, was undertaken to compare changes in reading and spelling as well as irregular and non-word reading skills after 3 months of wearing either the Harris or the DRT filters. RESULTS: Reading improved significantly after wearing either type of filter (t = -8.4, p < 0.01), with 40% of the children improving their reading age by 6 months or more during the 3 month trial. However, spelling ability (t = 2.1, p = 0.05) and non-word reading (f = 4.7, p < 0.05) improved significantly more with the DRT than with the Harris filters. CONCLUSION: Education and rehabilitation professionals should therefore, consider coloured filters as an effective intervention for delayed readers experiencing visual stress. IMPLICATIONS FOR REHABILITATION: Any disability that impacts on a child's capacity to read has serious implications for academic development as well as the ability to participate independently in activities of daily living. One reading disability, generally termed "visual stress", is related to visual disturbances that make it difficult to read text. This research demonstrates the beneficial use of coloured filters for promoting visual reading capacity for children with visual stress. Professionals who are involved in the needs of children with reading delay, may like to consider the benefits that coloured filters can afford children with visual reading problems.